Culpeper’s Impoliteness Strategies in Selected British Actors’ Interviews: A pragmatic Analysis - Naser Abbas, Abeer; Muhsin, Ali (Journal of College of Education, 2019)
This research examines impoliteness that is employed in selected British actors’ interviews by using pragmatic approach. The research aims at pinpointing the most common impoliteness strategies and showing the types of impoliteness in the data of the current study. Culpeper’s (1996) model of impoliteness is used to achieve the aims of the present study. The research employed the qualitative method. The study has come up with certain concluding remarks. The study has revealed that some of impoliteness strategies and all types of impoliteness are used in used in selected British actors’ interviews.